“Intelligent” Pt Catalysts Based on Thin LaCoO3 Films Prepared by Atomic Layer Deposition - Mao, Xinyu; Foucher, Alexandre C.; Stach, Eric A.; Gorte, Raymond J. (Inorganics, 2019)
LaCoO3 films were deposited onto MgAl2O4 powders by atomic layer deposition (ALD) and then used as catalyst supports for Pt. X-ray diffraction (XRD) showed that the 0.5 nm films exhibited a perovskite structure after redox cycling at 1073 K, and scanning transmission electron microscopy and elemental mapping via energy-dispersive X-ray spectroscopy (STEM/EDS) data demonstrated that the films covered the substrate uniformly. Catalysts prepared with 3 wt % Pt showed that the Pt remained well dispersed on the perovskite film, even after repeated oxidations and reductions at 1073 K. Despite the high Pt dispersion, CO adsorption at room temperature was negligible. Compared with conventional Pt on MgAl2O4, the reduced forms of the LaCoO3-containing catalyst were highly active for the CO oxidation and water gas shift (WGS) reactions, while the oxidized catalysts showed much lower activities. Surprisingly, the reduced catalysts were much less active than the oxidized catalysts for toluene hydrogen. Catalysts prepared from thin films of Co3O4 or La2O3 exhibited properties more similar to Pt/MgAl2O4. Possible reasons for how LaCoO3 affects properties are discussed.